Soil-Structure Interaction of a Piled Raft Foundation in Clay â a 3D Numerical Study - Susila, Endra; Anggraini, Nita (Journal of Engineering and Technological Sciences, 2016)
Piled raft foundation designs consider the contribution of the pile cap in transferring load to the ground and distributing load over the piles. The concept of a piled raft foundation requires a comprehensive evaluation of a number of factors that affect the performance of the foundation system. In this research the interaction among piles, pile cap and soil of a piled raft system on medium and stiff clays was studied. The effects of various distances between piles (s/d) in affecting load transfer mechanisms and deformation were considered. The study was performed by utilizing the 3D finite element method with a professional software package called Plaxis3D Foundation. A case study of the piled raft foundation performances of a foundation design for a high-rise building based on the soil stratification in Jakarta was also performed and is presented in this paper.